Sumber-Sumber Self Efficacy dalam Mengajarkan Critical Thinking - Gusti Ayu Ryana Mahasari (Edukasi: Jurnal Pendidikan Dasar, 2021)
This study aims to measure the predictive power of the four sources of self-efficacy on self-efficacy teaching critical thinking in prospective MIPA teachers at Ganesha University of Education. This study collected 202 respondents from various study programs in mathematics education, physics education, chemistry education, biology education, and science education with semester levels and different teaching practice experiences. The research method uses a survey in the form of an online and offline questionnaire. The result, the four sources of self-efficacy have predictive power that is quite strong and has a contribution of 45.2% to self-efficacy teaching critical thinking. However, the source that predicts the strongest is not in the mastery experience variable according to the researchers' hypothesis statement but emotional arousal. The discussion of these results begins by looking at the background of the respondents who are prospective teachers so that the respondents do not have much teaching experience, especially teaching success. Other findings also discussed in this study that GPA, semester level, and teaching practice experience of prospective MIPA teachers do not have a correlation with self-efficacy teaching critical thinking